Konsep Analisis Rasio Aktivitas Dan Profitabilitas Keuangan Perusahaan - Ahmad Purbaja (STAI Publisistik Thawalib Jakarta, 2022)
The research objective is to describe and explain the concept of activity ratio analysis and company financial profitability. Qualitative research methods with a library study approach. Data collection techniques with documentation studies. Data processing techniques with reduction and presentation of data. The results showed: (1) activity ratio analysis, namely: (a) Inventory turnover, which shows the company's financial ability for one round to finance inventory. (b) Fixed Assets Turn Over, to find out how much funds are used to finance inventories in a certain period (3). Total assets turnover, to determine the strength of capital in assets during a certain period. (2) analysis of profitability ratios, namely: (a) net profit margin, to determine the amount of profit earned by the company. (b) return on investment, namely the ability to gain profits through the utilization of its assets. (c) return on equity to find out the amount of funds returned in obtaining profits.